Bactericidal effect of various non-thermal plasma agents and the influence of experimental conditions in microbial inactivation: A review - Guo, Jian; Huang, Kang; Wang, Jianping (Food control, 2015)
Microbial inactivation using non-thermal gas discharge at atmospheric pressure has become a subject of significant research effort in the recent years. In this paper, we reviewed the different viewpoints proposed by various researchers, and discussed the reasons for arriving at these conclusions. We summarized some general rules, and offered a proposal to study the reasons behind their conclusions by building mathematical model for prediction of principle factors. The future prospects for the application of plasma are outlined. •The relationship between plasma types and the plasma agents' roles was summarized.•The influence of experimental conditions on microbial inactivation was discussed.•The interaction mechanism of charged particles with microorganism was reviewed.•The mathematic prediction model for the experiments was proposed.